2011
DOI: 10.1007/s11606-011-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Distal and Proximal Colonic Neoplasia: A Meta-Analysis

Abstract: OBJECTIVESTo investigate the association between proximal colonic neoplasia and distal lesions as a function of the lesion type. The extent to which health, demographic, and study characteristics moderate this association was also examined.DATA SOURCESGoogle Scholar, Web of Science, Scopus, and PubMed.STUDY ELIGIBILITY CRITERIAStudies allowing the calculation of OR of proximal neoplasia(PN) and proximal advanced neoplasia (PAN) for distal hyperplastic polyps (HP), nonadvanced adenomas (NAA), adenomas (AD), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Many of these patients, however, are also known to have more distal lesions that will be detected during FS and followed by colonoscopy. A recent meta-analysis showed that more than half of proximal neoplastic colonic lesions occurred isolated, i.e., in patients without concurrent distal polyps or CRC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients, however, are also known to have more distal lesions that will be detected during FS and followed by colonoscopy. A recent meta-analysis showed that more than half of proximal neoplastic colonic lesions occurred isolated, i.e., in patients without concurrent distal polyps or CRC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous studies [20][21][22] , our data showed that distal adenomas, but not distal hyperplastic polyps, were associated with increased risk for APN. Moreover, distal neoplasia, including advanced neoplasia and non-advanced adenoma, are consistently found to be risk factors of APN 23 . The OR of distal advanced neoplasia for APN was 2.7-3.6 when compared with normal distal findings 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk algorithms devised for prediction of APN 13,15,[19][20][21][22][23][24][25] . These risk models used different criteria to estimate the risk of APN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant findings at flexible sigmoidoscopy should trigger a complete colonoscopy, a considerable number of patients with advanced proximal adenomas do not have a synchronous distal lesion. 39 …”
Section: Flexible Sigmoidoscopymentioning
confidence: 99%